2005
DOI: 10.1111/j.1742-4658.2005.04872.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein glycation in Saccharomyces cerevisiae

Abstract: Methylglyoxal is the most important intracellular glycation agent, formed nonenzymatically from triose phosphates during glycolysis in eukaryotic cells. Methylglyoxal‐derived advanced glycation end‐products are involved in neurodegenerative disorders (Alzheimer's, Parkinson's and familial amyloidotic polyneurophathy) and in the clinical complications of diabetes. Research models for investigating protein glycation and its relationship to methylglyoxal metabolism are required to understand this process, its imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
2
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(90 citation statements)
references
References 36 publications
2
83
2
1
Order By: Relevance
“…Yeast, in contrast to bacteria, are capable of higher forms of posttranslational modifications including glycosylation although 12 there are considerable differences observed between the glycan structures of yeast and mammalian origin. Yeast glycan structures are typically represented as high-mannose types, or as non-enzymatic glycation (glucose) products [30,31]. Accordingly, mannose, along with galactose and glucose, were observed as the major monosaccharides from this extract.…”
Section: Resultsmentioning
confidence: 99%
“…Yeast, in contrast to bacteria, are capable of higher forms of posttranslational modifications including glycosylation although 12 there are considerable differences observed between the glycan structures of yeast and mammalian origin. Yeast glycan structures are typically represented as high-mannose types, or as non-enzymatic glycation (glucose) products [30,31]. Accordingly, mannose, along with galactose and glucose, were observed as the major monosaccharides from this extract.…”
Section: Resultsmentioning
confidence: 99%
“…Comparative studies on the importance of glyoxalase system with that of aldose reductase enzymes in yeast have shown that during oxidative stress conditions when the glutathione levels are low, aldose reductase converts methylglyoxal to acetol in NADPH dependent way (Ponces Freire et al, 2003;Gomes et al, 2005). Studies on the metabolism of 2-oxoaldehydes by glyoxalase and aldose reductase in human have shown that aldose reductase can reduce glutathione conjugates of methylglyoxal (Cagen and Pisano, 1979;Ramana et al, 2000).…”
Section: Discussionmentioning
confidence: 97%
“…Aldose reductase has broad substrate specificity. It has been shown that in yeast, during oxidative stress conditions, the glutathione levels are depleted and the glyoxalase enzymes are inactive, aldose reductase then detoxifies about 40% of the methylglyoxal in the cell (Ponces et al, 2003;Gomes et al, 2005). In liver, where the glutathione levels are high, glutathione dependent glyoxalase pathway is preferred over the NADPH dependent aldose reductase pathway.…”
Section: Introductionmentioning
confidence: 98%
“…166 Consistentemente, observou-se glicação de proteínas promovidas por metilglioxal em Saccharomyces. 167,168 Diferentemente de bactérias, a principal via de formação do metilglioxal em leveduras pode ser a decomposição química espontânea da di-hidroxicetona fosfato, pois não foi detectada atividade de metilglioxal sintetase. 164 Recentemente, análises do genoma de S. cerevisiae não revelaram sequências homólogas à da metilglioxal sintetase, o que corrobora trabalhos anteriores.…”
Section: Metilglioxal Em Levedurasunclassified